Ethnic food consumption intention: a groundwork study on consuming Dayak food using theory of planned behaviour - Ting, Hiram; Chuah, Francis Chin Wei; de Run, Ernest Cyril; Phung, Melissa; Cheah, Jacky Jun Hwa (2015)
Despite being comfortable with customary food, consumers are willing to explore varieties of food from diverse cultures. While there is abundance of literature on food consumption, little is known about ethnic food consumption intention in Malaysia with theoretical explanation. The present study serves as groundwork to investigate the intention to consume Dayak food and the moderating effect of food neophobia with theory of planned behaviour as the underpinning basis. Quantitative questionnaire is adopted and 161 respondents are sampled. Structural equation modeling using partial least squares approach is utilized to assess relationships between variables and moderation effect. Subsequently, attitude, subjective norm and perceived behavioural control are found to have significant relationships with ethnic food consumption intention. However, food neophobia does not moderate any relationship. The study highlights the importance of understanding ethnic food consumption intention and calls for further investigation to extend the knowledge on the subject matter.